American Civil Liberties Union of Northern California Honors Howard Watkins with Lola Hanzel Courageous Advocacy Award - Watkins, Howard::::::::: (1987)
Nancy Pemberton, Lee Halterman, Dorothy Ehrlich, Howard Watkins and Christine Watkins Luncheon at Sheraton Palace Hotel in San Francisco